2016
DOI: 10.1159/000443445
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II Induces ER Stress and EMT and Increase Extracellular Matrix Production in Renal Tubular Epithelial Cell in Early Diabetic Mice

Abstract: Background/Aims: Urotensin II (UII) and its receptor are highly expressed in the kidney tissue of patients with diabetic nephropathy (DN). The aim of this study is to examine the roles of UII in the induction of endoplasmic reticulum stress (ER stress) and Epithelial-mesenchymal transition (EMT) in DN in vivo and in vitro. Methods: Kidney tissues were collected from patients with DN. C57BL/6 mice and mice with UII receptor knock out were injected with two consecutive doses of streptozotocin to induce diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…It has been demonstrated that ER stress can induce EMT regardless of the tissue of origin or malignant status of cells (Shah, Dupre, Siskind, & Beverly, ), and Scr‐dependent signaling may play a role (Moon, Kim, Nho, Jang, & Lee, ). Both Tang et al () and Pang et al () found that ER stress can induce EMT in HK‐2 cells. In this study, we found salubrinal, an inhibitor of ER stress, blocked miR‐4756‐induced EMT, which indicates that miR‐4756 regulates HK‐2 EMT partly through ER stress.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been demonstrated that ER stress can induce EMT regardless of the tissue of origin or malignant status of cells (Shah, Dupre, Siskind, & Beverly, ), and Scr‐dependent signaling may play a role (Moon, Kim, Nho, Jang, & Lee, ). Both Tang et al () and Pang et al () found that ER stress can induce EMT in HK‐2 cells. In this study, we found salubrinal, an inhibitor of ER stress, blocked miR‐4756‐induced EMT, which indicates that miR‐4756 regulates HK‐2 EMT partly through ER stress.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, endoplasmic reticulum (ER) stress and the epithelial‐to‐mesenchymal transition (EMT) have been identified as key effects in tubulointerstitial fibrosis, thereby accelerating the progression of DKD (Maekawa & Inagi, ; Ravindran, Kuruvilla, Wilbur, & Munusamy, ). Several factors, including proteinuria, can trigger ER stress and EMT during the development of DKD (Allouch & Munusamy, ; Pang et al, ). Proteinuria is a key factor for promoting the progression of DKD.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype identification of UT gene knockout mice was performed by PCR according to our previous publications [6]. Lane 1 in Figure 6 (−/−) represents homozygotes of UT gene knockout (KO group) genotype; lanes 2 and 9 (+/−) represent heterozygotes of UT gene knockout; lane 10 (+/+) represents wild type (WT).…”
Section: Resultsmentioning
confidence: 99%
“…Amplification 756 bp means urotensin II receptor is knocked out and 63 bp means wild type; both 756 bp and 63 bp mean heterozygotes of UT gene knockout KO mouse as well as mRNA and protein expression of UT KO group, according to our previous publications [6]. …”
Section: Methodsmentioning
confidence: 99%
“…Epithelial cells that are subjected to ER stress often lose epithelial features (for example E cadherin) and may acquire markers of mesenchymal (myofibroblastic) lineage such as vimentin, N‐cadherin, and α‐smooth muscle actin, in a process that recapitulates more or less the epithelial‐to‐mesenchymal transition observed in cancer. Incomplete EMT, also refereed as epithelial phenotypic changes (EPC), participates in the whole fibrotic process upon tissue injury in proportions that vary according to the model [Cuevas et al., ; Moon et al., ; Pang et al., ]. The specific contribution of these cells in fibrogenesis includes the production of extracellular matrix, and secretion of profibrotic mediators.…”
Section: Er Stress In the Progression Of Chronic Kidney Diseasementioning
confidence: 99%